Changing trends in glaucoma surgery within Australia. Issue 7 (17th February 2021) - Sun, Michelle T; Madike, Reema; Huang, Sonia; Cameron, Cassie; Selva, Dinesh; Casson, Robert J; Wong, Christopher X
Abstract : Background: Limited data are available on glaucoma surgical trends in Australia. Methods: Nationwide study of glaucoma surgery in Australia over 17-year period from 2001 to 2018. The Australian Institute of Health, Welfare and Ageing hospitalisation database was used to review age- and gender-specific trends in glaucoma surgeries from 2001 to 2018 in Australian public and private hospitals. Results: Although there was an increase in the absolute number of trabeculectomy procedures from 2926 to 3244 over the 17-year study period, this represented a decline in the age-standardised and gender-standardised number of trabeculectomy procedures from 15.1 to 13.2 procedures per 100 000 persons. However, during this same period, there was a dramatic increase in the number of glaucoma drainage devices (GDD) from 119 to 3262 procedures, representing an age-standardised and gender-standardised increase from 0.6 to 13.3 procedures per 100 000 persons. Negative binomial regression analysis revealed a decrease in trabeculectomy procedures of 1.1% per year, while there was increase in GDD insertions of 16.3% per year (p<0.001 for both). When stratified by age group, there was a statistically significant interaction in both trabeculectomy and GDD rates by age groups over time (p<0.001 for both). Trabeculectomy procedures decreased to a greater extent in those aged >60 years, compared with stable or increasing rates in younger age groups. GDD insertion rates demonstrated a progressively greater increase in older compared with younger age groups. Conclusion: Our findings demonstrate changing trends in the surgical management of advanced glaucoma in Australia, likely reflecting updated evidence regarding the role of GDD surgeries.